Evaluation of cytotoxicity of 3.8 % SDF and BioAKT solutions on the viability of dental pulp stem cells - Viral Maru; Mohammed Ismail B; Akshayraj Langaliya; Bhuvaneshwari Karthikeyan; Syeda Habiba (Elsevier, 2024)
Introduction: Nonsurgical endodontic therapies have evolved from classic endodontic therapies to regenerative endodontic treatments (RETs) in recent years. In context of the cytotoxic activity of the most commonly used endodontic irrigant, NaOCl, newer endodontic irrigating solutions should be tested for its effective use in RETs. The aim of this trial was to examine and assess the cytotoxic response of 3.8 % SDF and BioAKT irrigating solutions on the viability of DPSCs. Methods: The viability of DPSCs cultivated in 5.25 % NaOCl, 3.8 % SDF & BioAKT at dilutions of 1:100,1:20 &1:10 were evaluated through MTT assay after 10 min, 60 min and 24 h incubation, detection of apoptosis and ALP activity after 7,14 & 21-days incubation. A two-way analysis of variance (ANOVA) with post hoc Turkey HSD was performed to determine significant differences between the specimens tested. Results: When compared to the control at all time periods, all test specimens at varied dilutions (1:100, 1:20, and 1:10) caused no cytotoxic effects. The maximum number of live cells and ALP activity was observed with DPSCs cultivated in BioAKT followed by 3.8 % SDF and 5.25 % NaOCl at all time intervals. Conclusion: Different doses of 3.8 % SDF and BioAKT solution revealed encouraging outcomes when compared to 5.25 % NaOCl in terms of viability, proliferation and long-term ALP functioning potential when cultivated in DPSCs.